2017
DOI: 10.3892/ol.2017.6327
|View full text |Cite
|
Sign up to set email alerts
|

Association of p73 gene G4C14-A4T14 polymorphism and MDM2 gene SNP309 with non-small cell lung cancer risk in a Chinese population

Abstract: Abstract. The present study aimed to investigate the association of p73 G4C14-A4T14 polymorphism and murine double minute 2 (MDM2) 309 T/G single nucleotide polymorphisms (SNPs) with the risk of developing non-small cell lung cancer (NSCLC) in Sothern China. The p73 and MDM2 genotypes of peripheral blood DNA from 186 patients with NSCLC and 196 normal controls were detected by polymerase chain reaction (PCR) with confronting two-pair primers (CTPP) and high resolution melting (HRM), respectively. The results o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…The literature search resulted in the identification of 239 documents: 78 studies were excluded after duplicates were removed, and 112 papers were excluded after review of titles and abstracts. The full text of the 49 remaining publications was screened, and, finally, nine studies including 3543 cases and 4435 control individuals were included 18–22,35–38 . The flow chart of the meta‐analysis is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…The literature search resulted in the identification of 239 documents: 78 studies were excluded after duplicates were removed, and 112 papers were excluded after review of titles and abstracts. The full text of the 49 remaining publications was screened, and, finally, nine studies including 3543 cases and 4435 control individuals were included 18–22,35–38 . The flow chart of the meta‐analysis is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Data on the contribution of MDM2 SNP309 to the development of lung cancer are very contradictory. Most studies have shown an association of the MDM2 (rs2279744) mutant allele with a high risk of lung tissue carcinogenesis (Enokida et al, 2014;Wang X. et al, 2015;Li, 2017). However, Pine et al (2006) did not find that MDM2 SNP309 is associated with lung neoplasia in the European population.…”
Section: Introductionmentioning
confidence: 94%
“…nih.gov/gene/4193) (3). The effects of single nucleotide polymorphisms (SNP) at MDM2 have been investigated in relation to lung cancer with inconsistent results (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Previous epidemiology studies concerning MDM2 SNPs and lung cancer risk were mainly focused on single SNP and interactions (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). No systematical investigations have been reported on the associations between MDM2 htSNPs (Haplotype-tagging SNP) and lung cancer risk.…”
Section: Introductionmentioning
confidence: 99%